Development of retirement readiness measures based on the Capacity Willingness Opportunity Model - Haron, Sharifah Azizah (Universiti Putra Malaysia, 2024)
In an effort to avert the high old-age dependency ratio in Malaysia, the study reconceptualized and developed retirement readiness scales based on the Capacity Willingness Opportunity Model (CWOM). The developed scales emphasized the importance of capacity and opportunity as catalytic traits in a retirement preparatory process. The study adopted three phases of designing a scale meticulously- item development, scale development, and scale evaluation. This process involved qualitative and quantitative research approaches. In the pilot study, out of the 61 items loaded into the exploratory factor analysis (EFA), 27 items were retained based on items with reasonable inter-item correlation, and they yielded four components. This study applied a multistage sampling technique to collect data from an adult family member of students from a local university in Klang-Valley, Malaysia. Based on the four factors yielded by the EFA in the pilot study, the researchers conducted another EFA using Varimax rotation with the remaining items and discovered a similar result to the pilot outcome. Subsequently, a pooled confirmatory factor analysis on 27 items confirmed the psychometric properties of 17 newly developed indicators. Notably, the study contributes to the literature on the robustness of CWOM as a catalyst for retirement readiness and establishes the statistical compatibility of the constructs.